Mekka in the latter part of the 19th century : daily life, customs and learning, the Moslims of the East-Indian-archipelago - Hurgronje, C. Snouck 1857-1936. (Brill classics Islam, 2007)
From 1884-1885, Christiaan Snouck Hurgronje stayed in Mecca. He became intimately acquainted with the daily life of the Meccans and the thousands of pilgrims from all over the world. This volume deals with social and family life, funeral customs and marriage. It is a unique insight in one the most important places in islamic culture. With a new foreword by Jan Just Witkam